DISABLED PEOPLE EMPLOYMENT AS A CAREER REHABILITATION FORMS (Research Bulletins of the Faculty of Economic Sciences, 2021)
Similarly to many other countries all over the world, in Poland some affords are made to improve disabled people conditions to enhance their personal development and increase their participation in the life of society to the level of participation of healthy citizens. The article presents problems disabled people employment as a career rehabili-tation forms. The Polish model of complex rehabilitation considers all kinds of needs of a disabled person in the process of recovery. The full therapy process consists of psy-chological, medical, social and career rehabilitation. The division presented above is created only for methodological purposes as the rehabilitation process is continuous and its parts perfectly impose and complement themselves.
Keywords: disabled people, professional work, rehabilitation, professional activity, employment forms